ChemInform Abstract: A Convenient Synthesis of N, N‐Dimethylformamidines from Sulfonamides. Issue 39 (September 2015) - Chen, Yantao; Graden, Henrik; Aurell, Carl‐Johan; Gibson, James
Abstract The reaction tolerates electronically and sterically diverse N‐aryl arylsulfonamides, but is not applicable to alkyl substituted substrates.